Modal Sosial dalam Hari Raya Kurban: Pengembangan Kepercayaan Mudhohiterhadap Lasznas PPPA Daarul Qur’an Jakarta - Fadillah, Zulfan Arief; Amanulloh, Naeni (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2022)
builds trust in mudhohi, namely people who carry out sacrifices on Eid al-Adha. This research is focused on the pattern and process of forming mudhohi trust through social capital. This research is a qualitative research, with a qualitative descriptive approach. The theory used in this research is Robert D. Putnamâs theory of social capital which provides a summary of social capital. Putnam argues that social capital is part of social life which includes networks, norms, and beliefs. Data collection techniques used in this study were interviews, observation, and literature studies. The results of the interviews show that in general PPPA Daarul Qur'an  has utilized social capital in the process of implementing the qurbani program through strengthening the Al-Qur'an  glorification program. In the aspect of norms, three things are guaranteed by PPPA, namely animal health, implementation according to Sharia, and reports given to mudhohi. In terms of trust, PPPA absorbs the focus of the Qur'an based qurbani program, ordering sacrificial animals is easy, and reports are received in a timely manner. In terms of the network aspect, in building social networks in the PPPA Daarul Qur'an  qurban program, it divides into two networks, namely internal (bonding social capital) and external (bridging social capital and linking social capital). The social capital norms built by PPPA are able to provide trust. In addition, PPPA Daarul Qur'an  internal and external strategy in building a network of cooperation has succeeded in building the information flow of PPPA Daarul Qur'an  sacrifices and making it easy for mudhohi to sacrifice.